Pengaruh Integrasi Teknologi Digital Pada Model Pembelajaran PBL Untuk Meningkatkan Kemampuan Berpikir Kritis Siswa Sekolah Menengah - Utami, Davina Putri; Zalty, Rani Febriana; Kurniati, Nani (Yayasan Arfah Bin Haji Muhammad Saleh, 2025)
This study aims to systematically review the literature on the influence of the integration of Problem-Based Learning (PBL) with digital technology on the mathematical critical thinking skills of secondary school students. The method used is Systematic Literature Review (SLR) by examining primary studies obtained from Google Scholar, Scopus, and Web of Science published between 2020-2024. Articles were analyzed based on the year of publication, level of study, teaching materials, research methods, and research results. The results of the study show that the application of PBL based on digital technology is effective in improving students' critical thinking skills. The use of electronic LKPDs, digital pocketbooks, interactive e-modules, animated videos, and Classwiz emulators has been proven to support an active, collaborative, and meaningful learning process. The integration of digital technology in PBL not only increases the effectiveness of material delivery but also strengthens the internalization of concepts through learning experiences relevant to 21st century skills. This study concludes that PBL integrated with digital technology has a positive influence in improving the mathematical critical thinking skills of high school students.